2018
DOI: 10.1021/acschembio.7b00638
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Atropisomeric Factors Governing the Selectivity of Pyrimido-benzodiazipinones as Inhibitors of Kinases and Bromodomains

Abstract: Bromodomains have been pursued intensively over the past several years as emerging targets for the development of anticancer and anti-inflammatory agents. It has recently been shown that some kinase inhibitors are able to potently inhibit the bromodomains of BRD4. The clinical activities of PLK inhibitor BI-2536 and JAK2-FLT3 inhibitor TG101348 have been attributed to this unexpected polypharmacology, indicating that dual-kinase/bromodomain activity may be advantageous in a therapeutic context. However, for ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 39 publications
1
58
0
Order By: Relevance
“…ERK5 32 P-ATP kinase assay was performed as previously described, 12 with minor modifications to the reported protocol, with 50 μM [γ− 32 P]-ATP (500 cpm/pmol) and 200 μM PIMtide (ARKKRRHPSGPPTA) used as substrates. Briefly, compounds were tested in 12-point dose response, at a maximum concentration of 10 μM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK5 32 P-ATP kinase assay was performed as previously described, 12 with minor modifications to the reported protocol, with 50 μM [γ− 32 P]-ATP (500 cpm/pmol) and 200 μM PIMtide (ARKKRRHPSGPPTA) used as substrates. Briefly, compounds were tested in 12-point dose response, at a maximum concentration of 10 μM.…”
Section: Methodsmentioning
confidence: 99%
“…These molecules were initially developed to target the unrelated kinases LRRK2 and ERK5, respectively, and later discovered to also inhibit BET bromodomains. 11 12 LRRK2-IN-1 and XMD8–92 have been shown to reduce proliferation of human pancreatic cancer cell lines and murine Kras G12D pancreatic spheroids, and to exert cytostatic effects in murine xenograft models. 13 5 However, the pleiotropic effects of BRD4 bromodomain inhibition 14 and the abstruse role of ERK5 in oncogenesis 15 confound interpretation of these results.…”
Section: Introductionmentioning
confidence: 99%
“…This study also suggested that the ERK5 C-terminal domain is important for the biological function of ERK5 [64]. Heedful researchers have since used BRD4 inhibitors, such as JQ1, to delineate the role of BRD4 in their systems [25,45,55,56] and testing of ERK5 inhibitors against BRD4 is now an essential step in ERK5 drug discovery. Adding to the complexity, we have found that cpd 26 (XMD17-109) and AX15836, cause a conformational change in the kinase domain which leads to exposure of the C-terminal NLS and paradoxical activation of the ERK5 TAD [55] (see below and Figure 2).…”
Section: Development Of Mek5 and Erk5 Kinase Inhibitorsmentioning
confidence: 81%
“…MEK5-catalysed phosphorylation of the activation-loop TEY motif activates the ERK5 kinase domain, which subsequently drives autophosphorylation at multiple sites within the Continued C-terminus (Figures 1 and 2). This multi-site phosphorylation causes a pronounced reduction in mobility of ERK5 on SDS-PAGE gels [44,45]. Since this ERK5 'band shift' reflects kinase domain-catalysed autophosphorylation, its loss in cells treated with an ERK5i reports inhibition of ERK5 ( Figure 1A).…”
Section: The Challenge Of Monitoring Erk5 Inhibition In Cellsmentioning
confidence: 99%
See 1 more Smart Citation